2014
DOI: 10.1097/wnr.0000000000000234
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral and electrophysiological measures of the body inversion effect

Abstract: Previous behavioral and electrophysiological studies examining the body inversion effect, where inversion of a body stimulus reduces its recognition, suggested that information regarding human bodies is processed configurally. However, few studies to date have examined how the magnitude of the body inversion effect may be impacted by varying degrees of configural information present in a stimulus of interest. In the current study, upright and inverted body stimuli were presented across three body posture condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
14
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 29 publications
4
14
0
1
Order By: Relevance
“…The influence of stimulus presentation duration and stimulus discrimination difficulty during the body-inversion task on this perceptual bias was also examined. Consistent with previous research [ 48 49 ] an overall standard inversion effect was found for all healthy participants, as upright stimuli were processed more accurately than inverted stimuli. However, as hypothesised, this inversion effect was significantly weaker for those with high, as compared to low, BIC.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The influence of stimulus presentation duration and stimulus discrimination difficulty during the body-inversion task on this perceptual bias was also examined. Consistent with previous research [ 48 49 ] an overall standard inversion effect was found for all healthy participants, as upright stimuli were processed more accurately than inverted stimuli. However, as hypothesised, this inversion effect was significantly weaker for those with high, as compared to low, BIC.…”
Section: Discussionsupporting
confidence: 91%
“…This has been supported by research suggesting that the inversion effect weakens or disappears for headless body images, highlighting the significant role that faces play [ 28 , 29 , 30 ]. Nevertheless, this has not been well replicated, as other studies have shown substantial and similar inversion effects for both faces and headless bodies [ 6 , 31 , 32 ]. Similarly, literature has also suggested that bodies, like faces, are processed holistically and result in similar inversion effects [ 33 , 34 , 35 ].…”
Section: Introductionmentioning
confidence: 83%
“…The N170 is thought to be produced by the generation of global face configurations at the later stages of structural encoding ( Jacques & Rossion, 2007 ), while a delayed peak is elicited by images lacking these global features ( Eimer, 2000 ). Neurophysiological studies have also demonstrated similar irregularities in the N170 peak for body and object stimuli ( Rossion, Joyce, Cottrell, & Tarr, 2003 ; Tao, Zeng, & Sun, 2014 ).…”
Section: Introductionmentioning
confidence: 66%
“…These findings suggest that body postures may be processed in the configural manner, similar to face-processing, and that when body posture is inverted, participants exhibit impairments in processing such configural information (Reed et al, 2003). Research has demonstrated that these can be seen for a variety of different types of body postures (Brandman and Yovel, 2010;Tao et al, 2014;Arizpe et al, 2017). Electrophysiological studies demonstrate that, when body postures are inverted, the N170 component is delayed and its magnitude is enhanced (Minnebusch and Daum, 2009;Tao et al, 2014).…”
Section: Introductionmentioning
confidence: 88%
“…Research has demonstrated that these can be seen for a variety of different types of body postures (Brandman and Yovel, 2010;Tao et al, 2014;Arizpe et al, 2017). Electrophysiological studies demonstrate that, when body postures are inverted, the N170 component is delayed and its magnitude is enhanced (Minnebusch and Daum, 2009;Tao et al, 2014). In addition, to identify the specific part of the body that contributes to the inversion effect, studies have found that the body-inversion effect is eliminated when the head is removed from body-posture stimuli (Brandman and Yovel, 2010;Mohamed et al, 2011).…”
Section: Introductionmentioning
confidence: 99%